¿EL USO DE SOCRATIVE FOMENTA LA PARTICIPACIÓN Y EL APRENDIZAJE ACTIVO DEL ALUMNO?ANÁLISIS DESDE LA PERSPECTIVA DEL ALUMNADO (Revista educación, investigación, innovación y transferencia, 2022)
The new information and communication technologies (ICTs) have produced changes in society and consequently in education. ICTs allow the introduction of a new pedagogical approach, based on educational gamification through the implementation of various tools. In this context, the need arises to investigate the effect on students of the incorporation of these gamification processes. This work focuses on the use of the Socrative platform in the classes of the Customer Behavior subject of the Degree in Marketing and Market Research in order to improve the teaching-learning process. For this, and after implementing the use of the Socrative platform in the classes, a questionnaire was designed to find out the usefulness of the gamification technique used to improve student learning, their satisfaction with the activity and if they would recommend it. The results show that the use of Socrative has been perceived very positively by the students. Thus, students perceive various benefits derived from the use of this tool in teaching, which is why students have been satisfied with its use, expressing their interest in generalizing its use in other subjects.
Keywords: gamification; teaching; satisfaction; motivation; Socrative